ANALISA SISTEM MANAJEMEN LINGKUNGAN ISO 14000 DAN KEMUNGKINAN IMPLEMENTASINYA OLEH PARA KONTRAKTOR KELAS A DI SURABAYA - Herry Pintardi Chandra (Institute of Research and Community Outreach - Petra Christian University, 2002)
Sustainable construction development needs a good environmental management system. International standard ISO 14000 is one the standard of a good environmental management system. This research aims to obtain general idea on how far Class A contractors in Surabaya know about information, element, and the benefit of ISO 14000, and how to engage in analyzing environmental management system using Friedman and Wilcoxon Signed Rank Test. From the data analysis, it was shown that 64,71% of the respondents is aware of ISO 14000 and issue on work safety and health for employees has become a first priority (mean rank 8.09). This issue has been followed-up with the development of a proactive strategy (61.76%). The strategy is followed by tactic development among others is to check employees’ health in accordance to standard of work safety and health for employees which has been imposed by the government (mean rank 5.00). Abstract in Bahasa Indonesia : Konsep konstruksi berkelanjutan memerlukan sistem mana¬jemen lingkungan yang baik. Standar internasional ISO 14000 merupakan salah satu wahana untuk menjamin kinerja sistem manajemen lingkungan tersebut. Penelitian ini bertujuan untuk mendapatkan gambaran umum tentang sejauh mana para kontraktor kelas A di Surabaya menge¬tahui tentang informasi, elemen, dan keuntungan ISO 14000 serta bagaimana melakukan analisa sistem manajemen lingkungan tersebut dengan Friedman dan Wilcoxon Signed Ranks Test. Hasil analisa data menunjukkan 64,71% responden mengetahui informasi tentang ISO 14000, dan isu keselamatan dan kesehatan kerja karyawan menjadi prioritas utama (mean rank 8,09). Isu tersebut ditindaklanjuti dengan pengembangan strategi proaktif (61,76%), dimana strategi tersebut diikuti dengan pengembangan taktik antara lain memeriksa kesehatan karyawan sesuai dengan standard kesehatan yang telah ditentukan oleh pihak yang berwenang (mean rank 5,00).